Literature as a Pathway Toward Our Spirituality: Hartmann von Aue, Marie de France, and Heinrich Kaufringer - Classen, Albrecht (Classical Literature, 2024)
This paper critically examines several short verse narratives from the late twelfth and early fifteenth centuries in which the authors offered profound insights into the human quest for spirituality, identity, and meaning, and which continue to talk to us until today because they shed so much light on this fundamental quest in human life in philosophical, religious, ethical, and moral terms. They encourage us to turn our attention to pre-modern literature once again because the various poets offered timeless messages about human identity, culture, and values, maybe in a literary fashion that might allow us to gain deeper insights than countless contemporary narratives that are often extremely self-centered and superficial. I accept the risk of preaching to the converted because in reality at many universities or advanced schools all over the globe, the Middle Ages often do not even exist any longer as a topic of research and education because they seem to be irrelevant for the modern explorations of human life. However, almost four decades of teaching literature courses focusing on the pre-modern world have demonstrated to me that a sensible inclusion of medieval literature, whether in translation or in its original language, promises a considerable advancement in the universal quest for meaning in human existence because individual authors provided profound insights into the global question of what constitutes happiness and meaning.